y1 + y2 = 0
y1*y2 = -19
Step-by-step explanation:
The equation: y^2 - 19 = 0
Using Vieta's formula for equation in the form:
ax^2 + bx + c = 0
sum of roots = -b/a
Product of roots = c/a
Comparing the equation above with the equation in the question:
y^2 + 0x -19 = 0
coefficent of y^2 = a = 1
coefficient of x = b = 0
The constant = c = -19
![\begin{gathered} sumofroots=y_1+y_2 \\ \text{sum of roots = }(-0)/(1)\text{ = 0} \\ sum\text{ of roots = }0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3t8pe4qqw5uv0weuj96kqs67glpmx728xg.png)
![\begin{gathered} Productofroots=y_1* y_{2\text{ }}\text{= }(c)/(a) \\ \text{Product of roots = }(-19)/(1) \\ \text{product of root = -19} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a7l6c03du4t86h20985xoqcmf8k6t81z6k.png)
Hence:
![\begin{gathered} y_1+y_2=\text{ 0} \\ y_1* y_2\text{ = -19} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/njky6wb5l9r573zkj1o5jsjltktf3t259e.png)